EFEKTIFITAS PENGGUNAAN MEDIA PAPAN PENJUMLAHAN TERHADAP PEMAHAMAN KONSEP PENJUMLAHAN BERSUSUN SISWA KELAS II SDN CUKIR 1 JOMBANG - Khotimah, Khusnul; Susilo, Claudya Zahrani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effectiveness of the addition board media in improving second-grade students’ understanding of vertical addition concepts at SDN Cukir 1 Jombang. The study employed a quantitative approach using a pre-experimental one group pretest-posttest design. The sample consisted of 24 second-grade students. Data were collected through pretest and posttest instruments and analyzed using descriptive statistics and paired sample t-test. The results indicated a significant improvement in students’ conceptual understanding after the implementation of the addition board media. The average posttest score was higher than the pretest score, and the significance value was less than 0.05, indicating a statistically significant difference. The findings confirm that the use of concrete manipulative media effectively supports students in understanding place value and carrying procedures in vertical addition. This study implies that concrete learning media are essential in primary mathematics instruction to promote meaningful learning experiences aligned with students’ cognitive development stage.